Assignment of Usefulness of Physiotherapy Applied to Sports Training in the Case of Szczecin Swimmers - Wioletta Łubkowska; Elżbieta Sieńko-Awierianów; Jerzy Troszczyński (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2014)
The aim of this article is to make the assessment of physiotherapy use in the case of swimmers’ regeneration. A diagnostic survey was used as the method. Opinions from the author’s survey were considered and there were 30 high-class swimmers analyzed aged 15–27. The research was conducted in 2012 at the Floating Arena swimming pool in Szczecin. 100% of the surveyed swimmers benefit from regeneration after physical effort. The most common physiotherapist treatment in case of swimmers is dry classic massage – 86.7%. The water bath (63.3%), sauna bath (56.7%), whirl bath (53.3%), water jets/Scotch douche (43.3%) and hydro massages (30%) are the most common types of hydrotherapy. On the other hand, ultrasounds and cryotherapy are the least common treatments when choosing adequate types of regeneration, i.e. respectively 13.3% and 3.3%. The biggest amount of massages is performed shortly before start – 40%. Massage in 60% cases lasts 10 minutes. In 90% of the surveyed group partial massage is being applied, whereas only 3.3% of competitors take the overall massage. In case of 80% of the swimmers, massage is regarded as completely relaxing. For 77% of them it relaxes both physically and mentally. In case of 80% of the surveyed, it is regarded as the most efficient form of biological regeneration. 60% of swimmers say it is helpful to maintain readiness to start and to overcome fever (feeling of annoyance) or apathy.